Effects of exercise amount and intensity versus a combined exercise and lifestyle intervention on metabolic syndrome in adults with prediabetes: a STRRIDE-PD randomized trial - Bennett, William C.; Collins, Katherine A.; Johnson, Johanna L.; Slentz, Cris A.; Willis, Leslie H.; Bales, Connie W.; Huffman, Kim M.; Kraus, William E. (Frontiers in Physiology, 2023)
The purpose of this secondary analysis was to determine what portion of the effects of a Diabetes Prevention Program-like intervention on the metabolic syndrome (MetS) could be achieved with exercise alone, as well as determine the relative importance of exercise intensity and amount to the total exercise effect on the MetS. Sedentary, overweight adults with prediabetes were randomized to one of four six-month interventions: 1) Low-Amount/Moderate-Intensity (10 kcal/kg/week at 50% peak V ̇O2); 2) High-Amount/Moderate-Intensity (16 kcal/kg/week at 50% peak V ̇O2); 3) High-Amount/Vigorous-Intensity (16 kcal/kg/week at 75% peak V ̇O2); or 4) Diet (7% weight loss) plus Low-Amount/Moderate-Intensity (10 kcal/kg/week at 50% peak V ̇O2).The primary outcome of this secondary analysis was change in MetS z-score. A total of 130 participants had complete data for all five Adult Treatment Panel (ATP) III MetS criteria. The diet-and-exercise group statistically outperformed the MetS z-score and the ATP III score when compared to exercise alone. Aerobic exercise alone achieved 24% to 50% of the total effect of the combined diet-and-exercise intervention on the MetS score. Low-amount moderate-intensity exercise quantitatively performed as well as or better than the interventions of a greater amount at moderate intensity or vigorous intensity on MetS score. The combined diet-and-exercise intervention remains more efficacious in improving the MetS z-score. However, all three exercise interventions alone showed improvements in the MetS z-score; suggesting a modest amount of moderate-intensity exercise is all that is needed to achieve approximately half the effect of a diet-and-exercise intervention on the MetS.